Investigating How Student Interest and Teacher Competence Shape Science Education: Menyelidiki Bagaimana Minat Siswa dan Kompetensi Guru Membentuk Pendidikan Sains - Tristianti, Rosulita; Efendi, Nur (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the relationship between students' learning interest, perceptions of teacher competence, and cognitive learning outcomes in science education. Using a non-experimental quantitative approach with 90 randomly sampled students from a total population of 336, data were collected through questionnaires and analyzed using product moment correlation and multiple correlation. The results highlight significant correlations between students' learning interests, perceptions of teacher competency, and cognitive learning outcomes, emphasizing the importance of considering these factors in designing effective science education methodologies to enhance student engagement and optimize learning outcomes. Highlight: Engagement in science correlates with student interest in learning. Teacher competence impacts science learning outcomes significantly. Quantitative research informs effective science education methods. Keyword: Science Education, Student Learning Interest, Teacher Competence, Cognitive Learning Outcomes, Quantitative Research